Atomistic modeling of dislocation cross-slip in nickel using free-end nudged elastic band method. (15th April 2019) - Chen, Dengke; Costello, Luke L.; Geller, Clint B.; Zhu, Ting; McDowell, David L.
Abstract: Cross-slip of screw dislocations plays an important role in the plastic deformation of face-centered cubic (FCC) metals and alloys. Here we use the free-end nudged elastic band (FENEB) method to determine the atomistic reaction pathways and energy barriers of cross-slip in an FCC single crystal of Ni. We focus on the cross-slip process mediated by an array of pinning vacancy clusters in the form of stacking fault tetrahedra. We also study a competing process of screw glide by direct cutting of those pinning obstacles on the original slip plane. The activation energies of both cross-slip and obstacle-cutting are determined for different stresses, obstacle spacings and sizes. Using FENEB-calculated energy barriers, we construct dislocation mechanism maps to reveal the effects of resolved shear stress, obstacle spacing and size on the rate-controlling dislocation process for plastic deformation. We further evaluate the activation volumes of cross-slip and obstacle-cutting. The latter result emphasizes the notion of finite strength of the atomically sized pinning obstacles to dislocation motion and also validates the Nabarro scaling law of the linear dependence of activation volume on obstacle spacing. Graphical abstract: Image 1